Civic participation in rural areas of Poland and France - Debroux, Josette; Matuchniak-Mystkowska, Anna; Starosta, Paweł (Sociology of rural worlds in Poland and France: field research and studies, 2024)
Civic participation, otherwise called civic engagement (Pattie et al., 2003), is a subcategory of a broader concept of social participation (Misztal, 1977) and constitutes one of fundamental notions used in social sciences with regard to civil society. The objective of this article is to attempt to answer three main questions: 1. What was the general level of civic participation of the population living in rural areas in Poland and France at the end of the second decade of the 21st century and what was the extent of variations in participation between these two countries in that period? 2. What models of civic participation dominate among populations of rural areas in Poland and France? 3. Which of the following models: the socio-economic status model, the social capital model, or the attachment model is best suited to explaining variations in civic participation of Polish and French rural population? The empirical basis for answering those research questions is the database of the ninth edition of the European Social Survey conducted in 29 European countries in 2018, with 49, 519 participants. Our analysis was restricted to data with reference the population of rural areas in Poland (N = 664) and France (N = 688), with the total being 1352 respondents.